The effect of accretion temperature on microstructure and bending strength of atmospheric ice - Fallon, Chanel; Truyen, E.; Eakins, Daniel E.; Pervier, Hugo; Pervier, Marie Laure A.; Aceves Lopez, Maureen (Elsevier, 2023)
Accurate determination of the mechanical response of atmospheric ice is key to understanding the risks associated with ice impact on aircraft during flight. Two types of atmospheric ice which are of particular interest to the aerospace industry are studied. Rime and Glaze ice are each manufactured in an icing wind tunnel facility under controlled conditions. Rime ice is accreted at a temperature of −20◦C, and Glaze ice is accreted at −5 ◦C. Quasi-static threepoint bend tests are performed on both types of ice to understand the effect of accretion temperature, and therefore microstructure, on strength. The results indicate that the ice accretion temperature, and thus microstructure, has a significant influence on the bending strength. On average, the bending strength of Rime ice is 9.0 ± 0.18 MPa compared to 4.4 ± 0.093 MPa for Glaze. The comparatively lower accretion temperature of Rime results in smaller grain sizes and higher bending strength. In contrast, the effective modulus appears insensitive to ice microstructure, with an average value of 3.5±0.12 GPa for Rime compared to 3.6±0.098 GPa for Glaze. Furthermore, the results indicate that both the bending strength and effective modulus are insensitive to the ice storage time.
Keywords: ice; atmospheric; rime; glaze; bending; flexure